Therapeutic Properties of Bioactive Compounds from Different Honeybee Products - Cornara, Laura; Biagi, Marco; Xiao, Jianbo; Burlando, Bruno (Frontiers in Pharmacology, 2017)
Honeybees produce honey, royal jelly, propolis, bee venom, bee pollen, and beeswax, which potentially benefit to humans due to the bioactives in them. Clinical standardization of these products is hindered by chemical variability depending on honeybee and botanical sources, but different molecules have been isolated and pharmacologically characterized. Major honey bioactives include phenolics, methylglyoxal, royal jelly proteins (MRJPs), and oligosaccharides. In royal jelly there are antimicrobial jelleins and royalisin peptides, immunomodulatory MRJPs, and hydroxy-decenoic acid derivatives, notably 10-hydroxy-2-decenoic acid (10-HDA), with antimicrobial, anti-inflammatory, immunomodulatory, neuromodulatory, metabolic syndrome preventing, and antiaging activities. Propolis contains caffeic acid phenethyl ester (CAPE) and artepillin C, specific of Brazilian propolis, with antiviral, immunomodulatory, anti-inflammatory and anticancer effects. Bee venom consists of toxic peptides like pain-inducing melittin, SK channel blocking apamin, and allergenic phospholipase A2. Bee pollen is vitaminic, contains antioxidant and anti-inflammatory plant phenolics, as well as antiatherosclerotic, antidiabetic, and hypoglycemic flavonoids, unsaturated fatty acids, and sterols. Beeswax is widely used in cosmetics and makeup. Given the importance of drug discovery from natural sources, this review is aimed at providing an exhaustive screening of the bioactive compounds detected in honeybee products and of their curative or adverse biological effects.